2021
DOI: 10.1002/ajmg.a.62222
|View full text |Cite
|
Sign up to set email alerts
|

Genotype–phenotype correlation in Phelan‐McDermid syndrome: A comprehensive review of chromosome 22q13 deleted genes

Abstract: Phelan‐McDermid syndrome (PMS, OMIM #606232), also known as chromosome 22q13 deletion syndrome, is a rare genetic disorder characterized by intellectual disability, hypotonia, delayed or absent speech, motor impairment, autism spectrum disorder, behavioral anomalies, and minor aspecific dysmorphic features. Haploinsufficiency of SHANK3, due to intragenic deletions or point mutations, is sufficient to cause many neurobehavioral features of PMS. However, several additional genes located within larger 22q13 delet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 103 publications
(276 reference statements)
1
48
0
Order By: Relevance
“…Renal abnormalities were one of the most striking differences in our cohort (0% in Class I and sequence variants vs. 24% in Class II deletions), indicating that the renal abnormalities seen in PMS are not due to haploinsufficiency of SHANK3 . Recent literature has suggested CELSR1 as a candidate for the renal abnormalities seen in PMS ( 24 , 39 ). Among the individuals with renal abnormalities in our cohort ( n = 20), 16 had CELSR1 deleted.…”
Section: Discussionmentioning
confidence: 99%
“…Renal abnormalities were one of the most striking differences in our cohort (0% in Class I and sequence variants vs. 24% in Class II deletions), indicating that the renal abnormalities seen in PMS are not due to haploinsufficiency of SHANK3 . Recent literature has suggested CELSR1 as a candidate for the renal abnormalities seen in PMS ( 24 , 39 ). Among the individuals with renal abnormalities in our cohort ( n = 20), 16 had CELSR1 deleted.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Although SHANK3 haploinsufficiency resulting from pathogenic mutations 6 or deletions [7][8][9] have been associated with PMS characteristics, there have also been numerous studies where genes other than SHANK3 have been demonstrated to play contributory roles toward PMS symptoms. [8][9][10][11][12][13] The literature illustrates inconsistencies and gaps of knowledge about seizures in PMS, despite their relatively high frequency and significant clinical burden. Treatment guidelines for PMS include supportive care and management of comorbidities such as seizures.…”
mentioning
confidence: 99%
“…He was a carrier of a 25 kB duplication of the 9q34.3 chromosomal region that included NOTCH1 . Subjects with Phelan–McDermid syndrome usually appear to develop puberty at normal times [ 66 ]. NOTCH1 duplication may have caused the early onset of puberty in this patient.…”
Section: Clinical Evidence Demonstrates That Pubertal Onset May Be As...mentioning
confidence: 99%